Ustadz Kampung Pewaris Kiai Pondok: Kehidupan bersalaf di zaman modern - Prasetya, Budi (BINA' AL-UMMAH, 2019)
Life in this world has been going on for so long. From the hereditary life there has been a shift and inheritance-inheritance be it culture, science, religion, and much more. If the scholars inherited the knowledge possessed by the prophet, then Ustadz can be said to be the one who inherited the science of kiai. After being trained in the crater candradimuka named boarding school of the santri who will become ustad in their respective areas of course have the knowledge that has been given by the teacher. But in life related to economy or worldliness whether ustadz is able to imitate the way used by kiai with his zuhud, because that is done mostly is ngaji and da'wah, while today has entered the modern era, the era of globalization that pivot on the culture of consumptive.